1976
DOI: 10.1176/ajp.133.12.1409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lithium on impulsive aggressive behavior in man

Abstract: The authors conducted a double-blind, placebo-controlled study of the effect of lithium on aggressive behavior. The 66 subjects, who were prisoners in a medium security institution, ranged in age from 16 to 24 years, were physically healthy and nonpsychotic, and had histories of chronic impulsive aggressive behavior. Subjects received lithium or placebo daily for up to 3 months. There was a significant reduction in aggressive behavior in the lithium group as measured by a decrease in infractions involving viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Interestingly, previous studies have suggested that lithium may have strong anti-aggressive properties in humans [86,87] and anti-impulsivity properties in preclinical models [8890]. Notably, of all current treatments for BD, long-term lithium therapy is the only intervention associated with decreased rates of suicidal behavior and mortality in well-conducted meta-analytic reviews [9193].…”
Section: Endophenotypes and Potential Medication Targetsmentioning
confidence: 99%
“…Interestingly, previous studies have suggested that lithium may have strong anti-aggressive properties in humans [86,87] and anti-impulsivity properties in preclinical models [8890]. Notably, of all current treatments for BD, long-term lithium therapy is the only intervention associated with decreased rates of suicidal behavior and mortality in well-conducted meta-analytic reviews [9193].…”
Section: Endophenotypes and Potential Medication Targetsmentioning
confidence: 99%
“…The first modern use of lithium was for treatment of mania. 2 Lithium has also proven useful in major depression, particularly for augmentation of antidepressants; 9 for aggressive behaviour; 10,11 and it has a specific antisuicide effect. 12,13 Lithium’s prophylactic and antisuicidal effects are most unique – in these indications it is the most specific treatment in psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reviews the use of anticonvulsants, beta blockers and atypical antipsychotic agents has been described in detail [20,31,40-49]. For more than 40 years, lithium has been used in many populations to treat violence [50]. Serotonin reuptake inhibitors are commonly used in the setting of depression but can also be effective for reducing chronic anger [20].…”
Section: Discussionmentioning
confidence: 99%